Coronal dentin differs between young and mature adult humans: A systematic review. (December 2022) - Weerakoon, Arosha T.; Meyers, Ian A.; Thomson, David H.; Cooper, Crystal; Ford, Pauline J.; Symons, Anne L.
Abstract: Objective: This systematic review examines the effect of age on changes to coronal dentin properties. Design: Pubmed, Cinhal, Scopus, Web of Science and the Cochrane Database were searched for publications up to 31 December 2021. All studies were uploaded and reviewed using Covidence software. At different stages of the review, study selection and the extraction of data were completed by six independent reviewers based on the eligibility criteria. The quality of the articles was judged based on JBI Critical Appraisal Checklist for quasi-experimental studies. Results: Twelve studies satisfied the eligibility criteria and were included. Dentin characteristics and mechanical properties alter with age, and spatially within a tooth to depend on tubule orientation. Age-related mineral deposition within tubules, and collagen maturation in intertubular dentin compound the spatial effects on mechanical properties. Mechanical properties depend on collagen fiber orientation and apatite alignment relative to dentin tubules, characteristic differences in peritubular and intertubular dentin, and relative dentin tubule distribution within a tooth. The bulk of the research focussed on age-related apatite effects, although many reported limited understanding of changes to collagen, particularly in intertubular dentin. Conclusion: Investigations into the effect of age, depth, site and location on dentin collagen are warranted to minimize tooth loss in older populations by providing targeted adhesive, restorative or preventative interventions. Highlights: Increased mineral is attributed to apatite deposition within mature dentin tubules. Spatial tubule distribution affects mechanical test outcomes for both age groups. With age, dentin mineral to collagen ratios, hardness and stiffness increase. Advanced glycation end-products in collagen stiffens and hardens mature dentin. Relative to young, mature dentin is more brittle and prone to fracture.